Systematic Review: Sleep Disorders Based on Objective Data in Children and Adolescents Treated for a Brain Tumor - Helligsoe, Anne Sophie Lind; Weile, Kathrine Synne; Kenborg, Line; Henriksen, Louise Tram; Lassen-Ramshad, Yasmin; Amidi, Ali; Wu, Lisa Maria; Winther, Jeanette Falck; Pickering, Line; Mathiasen, René (Frontiers in Neuroscience, 2022)
Background: Tumors of the central nervous system (CNS) are the most common solid childhood malignancy. Over the last decades, treatment developments have strongly contributed to the improved overall five-year survival rate, which is now approaching 75%. However, children now face significant long-term morbidity with late-effects including sleep disorders that may have detrimental impact on everyday functioning and quality of life. The aims of this study were to 1) describe the symptoms that lead to polysomnographic evaluation; 2) describe the nature of sleep disorders diagnosed in survivors of childhood CNS tumor using polysomnography; and 3) explore the association between tumor location and diagnosed sleep disorder. Methods: An extensive literature search following the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines (PRISMA) was conducted. Inclusion criteria were children and adolescents diagnosed with a CNS tumor age < 20 years having a polysomnography performed after end of tumor treatment. The primary outcome was sleep disorder confirmed by polysomnography. Results: Of the 1,658 studies identified, 11 met the inclusion criteria. All the included articles were appraised for quality and included in the analysis. Analyses indicated that sleep disorders commonly occur among childhood CNS tumor survivors. Symptoms prior to referral for polysomnography were excessive daytime sleepiness, fatigue, irregular breathing during sleep and snoring. The most common sleep disorders diagnosed were sleep-related breathing disorders (i.e., obstructive sleep apnea) and central disorders of hypersomnolence (i.e., narcolepsy). Conclusion: Our findings point to the potential benefit of systematically registering sleep disorder symptoms among CNS tumor patients together with tumor type and treatment information, so that at-risk patients can be identified early. Moreover, future rigorous and larger scale controlled observational studies that include possible modifiable confounders of sleep disorders such as fatigue and obesity are warranted.